2017
DOI: 10.3945/jn.116.244079
|View full text |Cite
|
Sign up to set email alerts
|

Ambient UVB Dose and Sun Enjoyment Are Important Predictors of Vitamin D Status in an Older Population

Abstract: UVB-induced skin synthesis is considered the key source of vitamin D, yet exposure to UVB is poorly accounted for in epidemiological studies. The aim of this study was to examine the association of serum 25-hydroxyvitamin D [25(OH)D] concentration with accurately measured ambient UVB dose, sun enjoyment, supplements, and other factors. An all-Irish cohort of community-dwelling participants aged >60 y [median age: 73; 67% female; median 25(OH)D: 54.5 nmol/L] was used. Participants from this large, cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 44 publications
4
58
0
Order By: Relevance
“…Additionally, we did not have information on the duration individuals resided at the residence given; this is a limitation of this study as we calculated D-UVB dose based on their location of residence. We also unfortunately did not have 25(OH)D concentration, although strong relationship between D-UVB and 25(OH)D has been shown previously (15,44). While 25(OH)D is the best marker of vitamin D status at the time of blood draw, this provides little information about the average exposure over a prolonged period of time cancer takes to develop (45).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Additionally, we did not have information on the duration individuals resided at the residence given; this is a limitation of this study as we calculated D-UVB dose based on their location of residence. We also unfortunately did not have 25(OH)D concentration, although strong relationship between D-UVB and 25(OH)D has been shown previously (15,44). While 25(OH)D is the best marker of vitamin D status at the time of blood draw, this provides little information about the average exposure over a prolonged period of time cancer takes to develop (45).…”
Section: Discussionmentioning
confidence: 81%
“…This D‐UVB measure has also been corrected for many important factors which can considerably alter the D‐UVB dose reaching earth, such as cloud cover, ozone column and altitude. The strength of a similar D‐UVB measurement has been discussed in detail previously , and the D‐UVB used in this paper is of even greater special and temporal resolution . Furthermore, this ambient UVB dose took into account annual D‐UVB to get a “long‐term average” UVB dose for each individual, rather than a seasonally biased estimate, which would have been the case if a point estimate of vitamin D, such as 25(OH)D, was utilized.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Scragg et al also used this dosimeter, but also did not investigate vitamin D intake [40]. O'Sullivan et al estimated the daily ambient UVB dose for each participant in their study by using irradiated UV energy at various geographical points in Ireland and the residential address of the participants, and reported a relationship between it and serum 25(OH)D concentration [41]. Their estimation method differed from ours, which directly measured UV energy on the participants' arms.…”
Section: Discussionmentioning
confidence: 96%
“…A number of environmental factors, such as infections, vitamin exposure , the use of proton pump inhibitors , short duration of breastfeeding, parental smoking and changes in the gut microbium , have been reported to be involved in the pathogenesis of CD . It has also been suggested that ultraviolet B radiation influences the synthesis of vitamin D , which has been associated with the development of future CD . A study in the United States found that living in north versus south latitudes were associated with CD and this indicated that low levels of global radiation and cold weather could serve as risk factors for future CD.…”
Section: Introductionmentioning
confidence: 99%